Qualidade das águas subterrâneas rasas na Ilha de Cotijuba – Belém / PA - HANNA, Leila Maria Miranda (Universidade Federal do Pará, 2019)
The Island Cotijuba, approximately 12000 inhabitants and 60 km2, is bordered the Marajó Bay and Mamão hole. In much of the area occupied on the island, the sanitation is poor, with effluents in the soil or in cesspits, with the potential risk of contamination of groundwater, captured through shallow wells, for multiple uses, especially domestic consumption. The objective of this study was to evaluate the water quality of the water aquifer for human consumption; were analyzed temperature, pH, eletrical conductivity, turbidity, apparent color, total alkalinity, NH4+, N-NO3-, HCO3-, Cl-, SO42-, PO43-, total hardness, Na+, K+, Ca2+ and Mg2+, and total coliforms and Escherichia coli. The waters were characterized as the predominant ions and potability standards (2914/2011 / MS). Eighteen water wells were collected, with depths ranging from 4 to 33 m, held in April, August and November 2015, corresponding to the rainy season, transition and less rainy, respectively. They were measured in pH field, temperature, electrical conductivity and water level of wells. The other analyzes were performed in the laboratory of the Universidade Federal do Pará (UFPA). The topographic elevation was measured for making the Preferential direction of shallow groundwater flow map, having noticed that the central part of the island, toward, is composed of ground water recharge zone and the zone southwest (SW) is discharge area. The water is chlorinated with sodium, acidic and low mineralization, with a median of electric conductivity (EC), about 47μS / cm and pH ranging from 3.7 to 5.4; the highest levels of chemical constituents occur in the SW and northeast (NE) Island. They were obtained strong positive correlation ratios between sodium and chloride, and from ammonium and pH. Some wells showed parameters outside the potability standard, with wide variation, as the color (1 to 341 uH), turbidity (0.2 to 58.3 uT), chloride (1.06 to 255.24 mg / L Cl), iron (0.01 to 10.66 mg / L Fe) and ammonium (0.01 to 9 mg / L NH4+); total coliform occur in 67% of the transition period the samples to 100% of the rainy; E. coli was reported in 20% of samples of the rainy season and 29% of less rain. The nitrate was less than 10 mg / l NO3--N, maximum 6.9 mg / L. These values are associated with the sanitation system in situ and well built without proper techniques.